A Comprehensive Small-Signal Model Formulation and Analysis for the Quasi-Y Impedance-Source Inverter - Santos, Rafael [UNESP]; Rodrigues, Marcus V. M.; Arenas, Luis De Oro [UNESP]; Gonçalves, Flávio A. S. [UNESP] (MDPI, 2023)
This paper presents a detailed derivation of the small-signal model and components design considerations for the Quasi-Y-Source inverter. The design methodology is based on the converter steady-state operation, considering the impedance network inductor and capacitor voltage and charge balances, respectively. Moreover, the additional design criteria for component selection, considering control constraints and performance compromise, are given by parametric variation analysis based on converter dynamic response. The small-signal model and transfer functions are obtained using a state-space averaged model, including converter non-ideal characteristics given by equivalent-series resistances (ESR), which makes possible the proposition of different control strategies, using both single or multi-loop schemes. To demonstrate the usefulness of the proposed small-signal model, a DSP-based single-loop type-II PI control strategy is used in which the peak DC-link voltage is indirectly controlled through the measurement of the impedance network capacitor voltage. The controller and converter performances are verified with simulation and experimental results and successfully confirm the validity of the proposed dynamic model. Finally, the obtained results are validated with a built small-scale three-phase/three-wire inverter prototype.
Keywords: impedance-source networks; power electronics; Quasi-Y-Source; renewable energy; small-signal model